مفہوم المخالفۃ کی حجیت میں اصولیین کا اختلاف : ایک تحقیقی جائزہ: Disagreement of Uṣūliyyīn in the validity of Mafhūm al- Mukhālafah: A Research Review - Muhammad Abdun Naseer Alavi (Al-Qamar, 2019)
An important linguistical phenomenon that has been given great attention by Uṣūliyyīn is the concept of Mafhūm Al Mukhālafah (divergent meaning), because of its relation with the text of the Holy Qurān and the Sunnah. Mafhūm Al Mukhālafah can be defined as a meaning derived from the words of the text so that it departs from its explicit meaning. The views of Uṣūliyyīn differ in this regard; Ḥanafī Uṣūliyyīn are known not to accept Mafhūm Al Mukhālafah as evidence, they are basically of the view that Mafhūm Al Mukhālafah is not a valid method of interpretation. It must not be applied to a revealed text, namely the Holy Qurān and the Sunnah. As a method of interpretation, Mafhūm Al Mukhālafah is thus validated only with regard to a non-revealed text. Because there are many injunctions in the Qur’an and Sunnah whose meaning will be distorted if they were to be given divergent interpretation. On the other hand, Mutakallimīn Uṣūliyyīn are of the view that Mafhūm Al Mukhālafah in revealed text is acceptable only if it fulfills certain conditions.